2016
DOI: 10.1016/j.marpolbul.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

A comparative proteomic study on the effects of metal pollution in oysters Crassostrea hongkongensis

Abstract: The metal pollution has posed great risk on the coastal organisms along the Jiulongjiang Estuary in South China. In this work, two-dimensional electrophoresis-based proteomics was applied to the oysters Crassostrea hongkongensis from metal pollution sites to characterize the proteomic responses to metal pollution. Metal accumulation and proteomic responses indicated that the oysters from BJ site were more severely contaminated than those from FG site. Compared with those oyster samples from the clean site (JZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
1
8
0
1
Order By: Relevance
“…‘S ometsuke’ , an EPDR described in the abalone (a gastropod mollusc), has a role in shell biomineralisation and pigmentation [ 15 , 16 ], and EPDRs have also been found in mantle transcriptomes and shell proteomes in other mollusc species [ 17 19 ]. In addition, EPDRs have been implicated in gastropod larval development [ 20 ], are upregulated in response to toxins and metal pollution in bivalves [ 21 24 ], and are differentially regulated during pathogen challenge trials in bivalves [ 25 27 ] and in response to environmental stressors in both bivalves and gastropods [ 28 30 ]. Together, these studies are consistent with EPDRs having a diversity of functions, some of which appear to be lineage-specific.…”
Section: Introductionmentioning
confidence: 99%
“…‘S ometsuke’ , an EPDR described in the abalone (a gastropod mollusc), has a role in shell biomineralisation and pigmentation [ 15 , 16 ], and EPDRs have also been found in mantle transcriptomes and shell proteomes in other mollusc species [ 17 19 ]. In addition, EPDRs have been implicated in gastropod larval development [ 20 ], are upregulated in response to toxins and metal pollution in bivalves [ 21 24 ], and are differentially regulated during pathogen challenge trials in bivalves [ 25 27 ] and in response to environmental stressors in both bivalves and gastropods [ 28 30 ]. Together, these studies are consistent with EPDRs having a diversity of functions, some of which appear to be lineage-specific.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the 78 kDa glucose regulated protein was also up-regulated in another species of oyster C . hongkongensis sampled in Baijiao and Fugong sites severely contaminated by Cu (Xu et al, 2016). Besides BJ site, JS site was also heavily polluted by Cu, indicated by as high as 6 746.7 μg/g Cu (dry weight) concentrated in oysters (Ji et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…sikamea were collected from three sites (Baijiao (BJ); Jinshan (JS); Jiuzhen (JZ)) along the Jiulongjiang estuary, Fujian Province, China. Our previous study showed that JZ site was a relatively clean site and therefore regarded as a reference (Xu et al, 2016). Comparatively, both JS and BJ sites were severely polluted by multiple metals (especially copper and zinc) (Weng and Wang, 2014;Tan et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…It can also inactivate essential proteins by displacing Zn or Ca from the active sites [4], induce apoptosis and necrosis [17], and facilitate DNA mutagenesis through mismatch repair [18]. Finally, Hg is particularly prone to reacting with free-SH groups, inhibiting thereby the function of various proteins rich in thiols and depleting GSH levels [19]. Among trace metals, Hg is the most genotoxic agent, following the genotoxic potential order: Hg > Cu > Cd [13].…”
Section: Introductionmentioning
confidence: 99%